Effect of Meternal Stimulation According to MCH Book in Development of Children Aged 3 – 5 Years Old in Aisyiyah Bustanul Athfal Preschool and Kindergarten Surabaya, Indonesia - Irmansah, Badzlina Agastasya; Irwanto; Nining Febriyana; Hanna Dyahferi Anomsari (Universitas Airlangga, 2025)
The early developmental period in children is a crucial stage marked by rapid growth and development. The number of interconnected neurons can be observed to determine the quality of brain development in a child. Stimulation affects the connections between neurons. This research is an analytical, observational, cross-sectional study that aims to investigate the relationship between stimulation using the Mother and Child Health (MCH) book and the development of children aged 3–5 years at Aisyiyah Bustanul Athfal Preschool and Kindergarten, Surabaya. The sample for this research consists of 104 pairs of mothers and children aged 3–5 years old selected using a purposive sampling method. This research utilized primary data collected through a questionnaire based on the MCH book, completed by the mothers in the sample. A total of 79 children in the good stimulation category exhibit good development, while 21 exhibit deficient development. Meanwhile, four children in the deficient stimulation category show developmental delays. Fisher’s Exact Test shows a significant relationship (p-value = 0.003 < 0.05) with a weak relationship (C = 0.335) between maternal stimulation based on the MCH book and the development of children aged 3-5 years old in Aisyiyah Bustanul Athfal Preschool and Kindergarten, Surabaya. Therefore, it can be concluded that maternal stimulation, as outlined in the MCH book, has a significant impact on the development of children aged 3–5 years old in Preschool and Kindergarten Aisyiyah Bustanul Athfal Surabaya.